The Future of Banking : Strategic Alliances between Banks and FinTechs - Fofanov, Aleksandr (2022)
The impact of disruptive innovation-related modern information systems has recently changed the way businesses operate, resulting in positive implications for those willing to adapt. The digitization of financial services created opportunities for new entrants in the financial industry, known as FinTechs. FinTech refers to the use of modern technologies by nonbank businesses to deliver financial services through online software. Due to factors such as highly regulated environments and solid infrastructures, traditional banks have maintained their dominant positions in the financial service industry for a long time. Nevertheless, new entrants seek to challenge traditional banks and have the potential to reshape financial services in the near future.